Immune response and growth performance of crayfish Cherax quadricarinatus fed with supplementary diet of synbiotic - Amrullah, Amrullah; Wahidah, Wahidah (Indonesian Society of Scientific Aquaculture (ISSA), 2019)
ABSTRACT This study aimed to investigate the effectiveness of synbiotic (prebiotic alginate and probiotic bacteria Micrococcus spp) on the immune responses, growth performance, and bacterial resistance of freshwater crayfish. The experimental diets were formulated in three levels of synbiotic: the probiotic bacteria Micrococcus spp+100 mg/L alginate (Syn100), Micrococcus spp+200 mg/L alginate (Syn200), Micrococcus spp+300 mg/L alginate (Syn300), each level was mixed with tested feed. The basal diet (without synbiotics) served as the control diet. During 40 days of rearing, immune responses observations were conducted every 10 days, while the crayfish weight were recorded on day 40. Furthermore, the challenge test was performed against the pathogenic bacteria of A. hydrophila and reared for a week. The result showed that synbiotics treatment of Syn300 and Syn200 could improve the immune response and increased the growth rate (P<0.05). Both were also heavier than the Syn100 treatment. The highest resistance to A. hydrophila pathogenic bacteria by demonstrating a higher survival rate was Syn300 and followed by Syn200 (70.00 ± 0% and 73.33 ± 5.77%, respectively), compared to Syn100 (56.67 ± 3.33%) and the control (33.33 ± 3.33%). The synbiotic Micrococcus spp. combined with alginate potentially induced immune responses, increased growth performance, and improved bacterial pathogens resistance, making it an ideal synbiotic to be developed. Keywords: synbiotic, prebiotic, probiotic, Sargassum sp., alginate, brown algae ABSTRAK Penelitian ini bertujuan untuk menguji efektivitas penggunaan sinbiotik (prebiotik alginat dan probiotik Micrococcus spp) terhadap respons imun, performa pertumbuhan dan resistensi lobster air tawar. Tiga perlakuan sinbiotik yaitu Micrococcus spp+100 mg/L alginat (Syn100), Micrococcus spp+200 mg/L alginat (Syn200), Micrococcus spp+300 mg/L alginat (Syn300), masing-masing dicampurkan ke dalam pakan dan diberikan ke lobster. Pakan tanpa campuran prebiotik digunakan sebagai pakan kontrol. Selama 40 hari pemeliharaan, pengamatan respon imun dilakukan setiap 10 hari dan pada hari ke-40 pemeliharaan dilakukan pengukuran bobot lobster. Selanjutnya, lobster di uji tantang dengan bakteri A. hydrophila dan dipelihara kembali selama satu minggu. Hasil penelitian menunjukkan bahwa pemberian pakan yang mengandung sinbiotik Syn300 dan Syn200 dapat meningkatkan respon imun dan pertumbuhan (P<0.05) lebih tinggi dibandingkan dengan perlakuan Syn100, sementara bobot tubuh terendah didapat pada perlakuan kontrol. Resistensi lobster tertinggi terhadap bakteri A. hydrophila yang ditunjukkan dengan sintasan tertinggi didapatkan pada perlakuan Syn300 (70.00±0.00%) dan Syn200 (73.33±5.77%) dibandingkan dengan perlakuan Syn100 (56.67±3.33%) dan kontrol (33.33±3.33%). Penelitian ini membuktikan bahwa sinbiotik Micrococcus spp. yang dikombinasikan dengan alginat dapat menginduksi respons imun, meningkatkan performa pertumbuhan ,dan resistensi terhadap patogen sehingga merupakan sinbiotik yang ideal untuk dikembangkan. Kata kunci : sinbiotik, prebiotik, probiotik, Sargassum sp., alginat, alga coklat